Feasibility analysis of an off-grid photovoltaic-battery energy system for a farm facility - Damilola Elizabeth Babatunde; Olubayo Moses Babatunde; Micheal Uzoamaka Emezirinwune; Iheanacho Henry Denwigwe; Taiwo Emmanuel Okharedia; Oladele Julius Omodara (International Journal of Electrical and Computer Engineering (IJECE), 2020)
Renewable energy plays a very important role in the improvement and promotion of environmental sustainability in agricultural-related activities. This paper evaluates the techno-economic and environmental benefits of deploying photovoltaic (PV)- battery systems in a livestock farmhouse. For the energy requirements of the farm to be determined, a walkthrough energy audit is conducted on the farmhouse. The farm selected for this study is located in southern Nigeria. The National Renewable Energy Laboratory’s Hybrid Optimization Modeling for Electric Renewable (HOMER) software was adapted for the purpose of the techno-economic analysis. It is found that a standalone PV/battery-powered system in farmhouse applications has higher economic viability when compared to its diesel-powered counterparts in terms of total net present cost (TNPC). A saving of 48% is achievable over the TNPC and Cost of Energy with zero emissions. The results obtained show the numerous benefits of replacing diesel generators with renewable energy sources such as PV-battery systems in farming applications.